Pengaruh Kompetensi Sumber Daya Manusia dan Pengendalian Intern Terhadap Kualitas Laporan Keuangan di LPD se-Kecamatan Abiansemal - Mei Yadnya, I Komang Redite; Indraswarawati, Sang Ayu Putu Arie; Lesmana Putra, I Made Endra (Hita Akuntansi dan Keuangan, 2024)
It is claimed that financial reports possess good quality if the data articulated in the financial statements is comprehensible, devoid of deceptive ideas and significant mistakes, truthfully depicts the facts, and can be substantiated. Information that should be presented in local government financial reporting should be in by what is required by stakeholders. The objective of this research is to identify how human resource competency and internal control impact the accuracy of financial reports across LPDs in the Abiansemal sub-district. The study included all 32 LPDs in the Abiansemal District as the population, and a total of 97 participants were selected as the sample using purposive sampling technique. The research methodology involved the use of multiple linear regression analysis techniques to test the hypotheses.The findings of this research reveal that there is a favorable correlation between Human Resource Competence and Internal Control, and the accuracy of Financial Reports across all LPDs within the Abiansemal District. Looking at this research, it is hoped that in the future the LPDs throughout the Abiansemal District will be able to provide regular job training to employees related to the preparation of financial reports by accounting standards so that the abilities or competencies of employees will increase so that a good report is formed.Keywords: Competence of Human Resources, Internal Control, Quality of Financial Reports